Soluble MD-2 and Heme in Sickle Cell Disease Plasma Promote Pro-Inflammatory Signaling in Endothelial Cells - Zhang, Ping; Nguyen, Julia; Abdulla, Fuad; Nelson, Alexander T.; Beckman, Joan D.; Vercellotti, Gregory M.; Belcher, John D. (Frontiers in Immunology, 2021)
Recent evidence indicates that hemolysis in sickle cell disease (SCD) promotes inflammation via innate immune signaling through toll-like receptor 4 (TLR4). Free heme released by hemolyzed red blood cells can bind to myeloid differentiation factor-2 (MD-2) and activate TLR4 pro-inflammatory signaling on endothelium to promote vaso-occlusion and acute chest syndrome in murine models of SCD. MD-2 is co-expressed with TLR4 on cell membranes, but in inflammatory conditions, soluble MD-2 (sMD-2) is elevated in plasma. We examined sMD-2 in sickle (SS) plasma and its contribution to pro-inflammatory IL-8 production by endothelial cells. sMD-2 levels were significantly increased in human and murine SS plasma as compared to normal (AA) plasma. Human umbilical vein endothelial cells (HUVEC) exposed to human SS plasma had a 2-fold increase in TLR4-dependent IL-8 secretion as compared to HUEVC exposed to AA plasma. The increase in IL-8 in response to SS plasma was blocked by depletion of sMD-2 from SS plasma, addition of a TLR4 signaling inhibitor TAK-242, or addition of the high-affinity heme-binding protein hemopexin. Similarly, addition of recombinant sMD-2 to AA plasma increased IL-8 secretion. These data suggest that sMD-2 bound to heme might play an important role in pro-inflammatory signaling by endothelium in SCD.